A completely coated wedge crack interacting with a screw dislocation. (April 2020) - Wang, Xu; Schiavone, Peter
Abstract: We employ conformal mapping and analytic continuation to study the elastic field induced by a screw dislocation interacting with a completely coated semi-infinite wedge crack under mode III loading conditions. The screw dislocation can be located either inside the matrix or in the coating itself. Explicit expressions for the local wedge stress intensity factor and the image force acting on the screw dislocation are obtained. The dislocation emission criterion from the completely coated wedge crack is established.